2004
DOI: 10.1534/genetics.166.3.1187
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae Recombination Enhancer Biases Recombination During Interchromosomal Mating-Type Switching but Not in Interchromosomal Homologous Recombination

Abstract: Haploid Saccharomyces can change mating type through HO-endonuclease cleavage of an expressor locus, MAT, followed by gene conversion using one of two repository loci, HML or HMR, as donor. The mating type of a cell dictates which repository locus is used as donor, with a cells using HML and ␣ cells using HMR. This preference is established in part by RE, a locus on the left arm of chromosome III that activates the surrounding region, including HML, for recombination in a cells, an activity suppressed by ␣2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Although RE facilitates more frequent encounters between allelic sites on homologous chromosomes in MATa diploids (Bressan et al 2004), Houston et al (2004) reported that RE did not stimulate interchromosomal recombination between heteroalleles. The difficulty of using a donor located in trans suggests that chromosomes could define territories in the yeast nucleus without being totally isolated from each other, as it has been described in other organisms (reviewed by Spector 2003;Taddei et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Although RE facilitates more frequent encounters between allelic sites on homologous chromosomes in MATa diploids (Bressan et al 2004), Houston et al (2004) reported that RE did not stimulate interchromosomal recombination between heteroalleles. The difficulty of using a donor located in trans suggests that chromosomes could define territories in the yeast nucleus without being totally isolated from each other, as it has been described in other organisms (reviewed by Spector 2003;Taddei et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…This finding reminds us of the mating-type switching-directionality regulation of the distantly related budding yeast, Saccharomyces cerevisiae. Budding yeast mating-type MATa2 factor binds to two closely located recognition motifs at RE (recombinational enhancer) region as a diamer to repress the RE function for donor choice during mating-type switching (Houston et al 2004;Coic et al 2006). The Mc binding to this putative promoter might activate swi2S transcription.…”
Section: A Model For Swi2l and Swi2s Factors Controlling Directionalitymentioning
confidence: 99%
“…Discrepancies between the results described by Chung et al [42] and here could be explained either by specificity of EOGT assays or due to the fact that in their experimental system targeted region ( THR4 gene) was located on the chromosome III between MAT and HMR a loci. Therefore, dense heterochromatin repressing HMLα and HMR a regions as well as chromatin dynamics that changes the accessibility of these two genes used as donors during MAT switching [8689] could also affect gene targeting. In agreement with our results, it has already been shown that Exo1 and Sgs1 inhibit BIR in both chromosome-break repair assay [45] and chromosome fragmentation assay with DNA fragments either linearized in vivo or introduced in the cell by transformation [44].…”
Section: Discussionmentioning
confidence: 99%